Strengthening Disaster Preparedness through DRRM-Integrated Pedagogical Practices - Paco, Eddie Bert (Azal Arts and Humanities, 2025)
This study examined how Disaster Risk Reduction and Management (DRRM)–integrated pedagogical practices strengthened disaster preparedness at Lagawe Central School. Specifically, it explored the instructional strategies used by teachers to integrate DRRM concepts into classroom instruction, the influence of these practices on learners’ disaster awareness and preparedness behaviors, teachers’ and school stakeholders’ perceptions of DRRM-integrated pedagogy, and the challenges encountered in its implementation. A qualitative descriptive research design was employed to generate in-depth and context-specific insights. Data were collected through semi-structured interviews with selected classroom teachers, the school DRRM coordinator, and school administrators, as well as through classroom observations and document analysis of lesson plans, DRRM action plans, and school safety reports. Purposive sampling ensured that participants had direct involvement in DRRM instruction and preparedness initiatives. The data were analyzed using thematic analysis, with triangulation enhancing the credibility and trustworthiness of the findings. The results revealed that DRRM concepts were consistently embedded in classroom instruction across subject areas through contextualized discussions, simulations, drills, and learner-centered activities. These pedagogical practices enhanced learners’ disaster awareness, preparedness skills, and safety-oriented behaviors. Teachers observed increased learner confidence, discipline, and responsiveness during emergency situations. Participants also expressed positive perceptions of DRRM-integrated pedagogy, recognizing its importance in fostering a culture of safety and resilience within the school. However, challenges such as limited instructional materials, insufficient training, and time constraints affected the sustainability and depth of DRRM integration. The study concludes that DRRM-integrated pedagogical practices play a crucial role in strengthening disaster preparedness in schools and highlights the need for sustained institutional support, teacher capacity building, and collaborative partnerships to maximize their educational impact.